Complete Digital Workflow for Mandibular Full‐Arch Implant Rehabilitation in 3 Appointments. Issue 6 (20th April 2021) - Papaspyridakos, Panos; De Souza, Andre; Bathija, Anshu; Kang, Kiho; Chochlidakis, Konstantinos
Abstract: The aim of this clinical report is to describe a complete digital workflow protocol for mandibular full‐arch implant rehabilitation from guided surgery to definitive prosthesis in only 3 appointments. This expedited protocol allows for guided implant placement with a system of stackable surgical templates and CAD/CAM prosthodontic rehabilitation using a digital workflow. At the first appointment, a guided implant placement protocol with the stackable template concept was done followed by immediate loading with a prefabricated interim prosthesis. At the same appointment, the Double Digital Scanning (DDS) technique was used for scanning, maxillomandibular relationship registration and virtual articulation. The anchor pins from guided surgery were used as fiducial markers for DDS data superimposition. At the second appointment, the prosthesis prototype was tried‐in and adjustments were made. At the third appointment, the definitive monolithic zirconia full‐arch prosthesis was delivered.